When subjects become objects: The lies behind the Milgram legend. (October 2015) - Baumrind, Diana
In her exposé of Milgram's deceptions in obtaining "informed consent" and "dehoaxing" his subjects, Perry reveals Milgram's deceit and misrepresentation in his dealings with colleagues as well as participants. Perry relies on evidence from Milgram's unpublished papers and transcripts of his experimental proceedings to support her pejorative judgment on Milgram's professional ethics. Although deception research, such as Milgram's, clearly violates the informed consent clause of the APA Code of Ethics, it remains a modus operandi in child development and social psychology research. I argue that deception research proscribes informed consent and infringes the fiduciary obligation of psychologists to be trustworthy, and should be prohibited rather than justified by a cost-benefit analysis, as is presently the case.